Licenciamento ambiental federal no Brasil: perspectiva histórica, poder e tomada de decisão em um campo em tensão - Aline Borges do Carmo; Alessandro Soares da Silva (Confins)
This paper analyses the construction of the Environmental Impact Assessment procedure and the implementation of the environmental licensing instrument in Brazil from a perspective of history, society, politics and both internal and external contexts that influenced the decision making process, which reflect in the definition of public policies on this area. The analysis attempts to understand the technical issues of the federal environmental licensing in Brazil, throughout the environmental issue history and the emergence of the main related legal instruments and finally approaches the public policies concerned with Environmental Impact Assessment (EIA) regarding the social, economical, and political contexts. Thus, the analytical axis of this paper is the decision making processes, which is related to the production of political subjects and education for the power. The analysis shows that events that are apparently external to the procedures performed by technicians responsible for assessing applications for federal environmental licenses influence in a decisive way the results of this technical work, although this influence is not always so obvious or straightforward, especially for lay views. In general, the article suggests that it is necessary to review the way it treats the technical and human relations during EIA process. The conclusion is that purely technical and scientific tools, although academically well accepted may not be enough to make a difference in this arena and that a broader view that understands the subtle relationships among politics, human relations and technical procedures should guide any attempt at intervention aimed at improving these procedures, both the EIA as a process, and the Environmental Licensing as administrative instrument. From this comes that, despite the apparent technical-scientific approach, illustrated by environmental studies in theory underpinning the EIA, decision-making is actually a reflection of the political game that permeates the entire process.